2021
DOI: 10.52223/jei3012104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Vulnerability of Farm Households to Flood Risk in Punjab, Pakistan

Abstract: Climate change is the most important challenge for developing as well as developed countries. Pakistan is a developing country and has faced different types of natural disasters such as floods in the last 10 years. The rural areas of Pakistan are adversely affected by floods, which cause significant losses to crops, assets, and the household members face illness, health problems, loss of family income, and displacement. Approximately, 7016 villages with a cropped area of 473998 acres have been affected only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Farmers of the study area had been seen mitigating the harsh effects of natural disasters at their farms by increasing stock of money savings (Table 3) to cater to their farming needs (purchase of inputs, young stock of animals) at the time of any future undesired happenings. This finding matches the findings of Manzoor (2021), who reported that 50% of the farmers relied on domestic savings to mitigate the flood risks, a diversified/mixed farming system similar to a previous study (Van et al, 2020) by balancing the production of major crops with minor crops (Rayhan and Grote, 2010). Savings and diversification actions of respondents further imply that they were taking flooding as a positive externality for farming in the long run through its reinforcing impact on soil fertility.…”
Section: Risk Mitigation Strategies At Farm and Household Levelssupporting
confidence: 89%
See 1 more Smart Citation
“…Farmers of the study area had been seen mitigating the harsh effects of natural disasters at their farms by increasing stock of money savings (Table 3) to cater to their farming needs (purchase of inputs, young stock of animals) at the time of any future undesired happenings. This finding matches the findings of Manzoor (2021), who reported that 50% of the farmers relied on domestic savings to mitigate the flood risks, a diversified/mixed farming system similar to a previous study (Van et al, 2020) by balancing the production of major crops with minor crops (Rayhan and Grote, 2010). Savings and diversification actions of respondents further imply that they were taking flooding as a positive externality for farming in the long run through its reinforcing impact on soil fertility.…”
Section: Risk Mitigation Strategies At Farm and Household Levelssupporting
confidence: 89%
“…The main threat to farming, according to the 4/5 th (80%) majority, was the recurring occurrence of floods. The finding that floods are the main weather-related risk was also highlighted in the study, similar to Manzoor (2021).…”
Section: Types Of Weather Related Riskssupporting
confidence: 79%
“…Living alone was the most common feature of household composition that studies have identified a source of vulnerability or susceptibility due to the lack of social connections or support that residing with others provide (28,42,46,49,57,73,85,93,95,100,112,118,165,182,194,198,206). Other household composition factors that were indicative of vulnerability include household type (25,42,43,75,108,111,117,118), marital status (26,43,96,126,184), family size (67,69,159,207), female headed households (158,173), family conflict (115,184), and percentage of homes with orphans (70).…”
Section: Household and Household Compositionmentioning
confidence: 99%